Comparison of Tuberculosis Knowledge Between Health and Non-Health Students - Wahyudi Wahyudi; Dinda R. Aulia; Dwi A. Putri; Fatima Fatima; Hanum Prahasti; Nurul Fauziah (Universitas Ibn Khaldun Bogor, 2024)
Tuberculosis or tuberculosis is one of the chronic diseases that are dangerous to health. Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis bacteria that attack the respiratory organs of the lungs. This study aims to determine the level of knowledge of students related to the comparison of tuberculosis knowledge between health and non-health students. This research is a descriptive quantitative research using survey methods. Data collection was carried out by questionnaire via Google form which was then analyzed to be able to describe the results of the study. The results obtained from this study show that health students have a very good level of knowledge about tuberculosis knowledge, namely at University A (34.3%) and University B (14.7%) compared to non-health students at University C (17.6%) and University D (33.3%)